The Results of Surgical Treatment for Cyclotropia - Sibel Kocabeyoğlu; E. Cumhur Şener; A. Şefik Sanaç (Türk Oftalmoloji Dergisi, 2012)
Pur po se: To describe the effectiveness of oblique muscle surgery for cyclodeviations with vertical deviations. Ma te ri al and Met hod: Twenty-two eyes of 17 patients with cyclotropia were included in the study. All cases were examined pre- and postoperatively. Vertical and horizontal deviations, eye movements and oblique muscle functions were measured with prism cover test, while the degree of cyclotropia was evaluated with double Maddox rod and fundus photographs. Surgical techniques were anterior transposition of the inferior oblique muscle, inferior oblique recession, superior oblique tenotomy and superior oblique tucking. Re sults: There were 6 males and 11 females. The mean age of the patients was 17.4±9.7 years (range: 6-34 years) and the mean follow-up time was 6.9±3.1 months (range: 3-12 months). Eight patients (47.1%) presented with superior oblique palsy. Seven patients had a concomitant horizontal deviation; 29.4% of the patients had esotropia and 11.7% of the patients had exotropia. Eight eyes underwent anterior transposition of the inferior oblique muscle, 8 eyes underwent inferior oblique recession, 2 eyes underwent superior oblique tuck, and 4 eyes underwent superior oblique tenotomy. Anterior transposition of the inferior oblique muscle and inferior oblique recession were found as effective procedures in the treatment of vertical deviations and cyclotropia, but there was no statistically significant difference between the two procedures. Dis cus si on: Anterior transposition of the inferior oblique muscle and inferior oblique recession were found as effective procedures in the treatment of vertical deviations and cyclotropia. Anterior transposition of the inferior oblique muscle was found to be more effective than inferior oblique recession in the treatment of inferior oblique overaction. (Turk J Ophthalmol 2012; 42: 38-42)